"Capturing the magic": identifying the active ingredients of a physical activity participation intervention for children and youth with disabilities. Issue 9 (24th April 2022) - Willis, Claire; Elliott, Catherine; Reid, Siobhan; Nyquist, Astrid; Jahnsen, Reidun; Bölte, Sven; Rosenberg, Michael; Girdler, Sonya
Abstract: Purpose: This study aimed to define the active ingredients of a participation-focused physical activity intervention for children and youth with disabilities. Materials and methods: An ethnographic approach was employed, triangulating participant observation, interviews and focus groups. Participant recruitment occurred through purposive sampling of staff employed at Beitostolen Healthsports Centre (BHC), and paediatric service providers visiting the centre. Interviews were transcribed verbatim and coded together with observation data. Secondary coding linked data to corresponding categories of the International Classification of Functioning, Disability and Health: Child and Youth version. Results: Thirteen staff from BHC and 7 paediatric service providers participated in the study. Fourteen active ingredients were identified and were characterised at the level of the intervention ( k  = 8), the organisation ( k  = 4), and the individual ( k  = 2). Within the ingredients, 53 unique ICF-CY categories were identified. Twenty-six categories belonged to the ICF-CY component of "environment, " and 26 categories to "activities and participation." No categories related to "body functions" or "body structures." Conclusions: The role of the environment, and specifically support and relationships, may be an essential consideration for enabling physical activity participation. Outcomes may guide program design and implementation to promote and sustain physical activity behaviours for children and youth with disabilities. Implications for rehabilitation: The active ingredients identified in this study may guide the design and implementation of programs to promote and sustain physical activity behaviours of children and youth with disabilities. Leadership qualities and strength-based attitudes may be key characteristics of organisational practice that optimise outcomes for children and families. A "relationship-centred" approach, i.e., a network of children, families, health professionals, peers, mentors, and services in the community, may support children and young people with disabilities to achieve their physical activity participation goals.